(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Although a lot of research has been done in the military field, the concept of combat vehicles has not yet been comprehensively explored. This article describes the results of scientific research conducted in this directio